Strain control of ferromagnetic thin films and devices - Parkes, Duncan Edward (2016)
Magnetic memory and logic technologies promise greater energy efficiency and speed than conventional, semiconductor-based electronics. To date, electrical current has been used to operate such devices, although voltage-control may be a more efficient way to control magnetisation. One route to achieving voltage control of magnetisation is to use a hybrid piezoelectric/ferromagnetic device in which a voltage applied to the piezoelectric induces a strain in the ferromagnetic layer, which in turn induces a magnetic anisotropy. In this thesis such hybrid devices are used to investigate the control of magnetisation by inducing uniaxial anisotropy in the ferromagnetic layer. One material that shows promise for use as the ferromagnetic layer is Fe81Ga19. This material is attractive since it contains no rare earth elements, and in bulk crystals has been shown to be highly magnetically responsive to strain. This thesis investigates the magnetic properties of epitaxial Fe81Ga19 thin films grown by molecular beam epitaxy and it is demonstrated that these thin films retain the attractive magnetostrictive properties previously observed in bulk crystals. The presence of strong cubic magnetocrystalline anisotropy in the layers is exploited to demonstrate the non-volatile switching of magnetisation using strain-induced anisotropy in the absence of an applied magnetic field. This thesis shows also the manipulation of magnetic anisotropies and control of the configuration of magnetic domains and domain walls in Fe81Ga19 at a range of different lateral dimensions, from50 μm to 1 μm. It is shown that as the lateral dimensions of the device structures studied are reduced the domain configuration appears more regular, and that strain-induced anisotropy is more able to control these domains. In wires around 1 μm in width it is shown that growth strain relaxation by lithographic patterning induces sufficient anisotropy to cause a change in the domain configuration of the wire studied. Finally, this thesis begins to investigate how inverse magnetostriction can be used to tune the behaviour of domain walls in wires 1 μm wide and narrower. Experimental control of the field required to depin a vortex domain wall from a notch in a 1 μm wide Co wire is demonstrated. Using micromagnetic simulations it is shown that a large degree of control over the depinning of domain walls from notches in wires 1 μm wide and narrower is possible. The influence of in plane uniaxial magnetic anisotropy on the domain wall velocity in wires supporting in plane transverse domain walls driven by an external magnetic field is also investigated. Work previously done on the effect of uniaxial anisotropy on domain wall velocities close to Walker breakdown is extended in this thesis and in investigating the velocity and structure at driving magnetic fields far above walker Breakdown a second peak in domain wall velocity is observed, a phenomenon previously observed in wide wires, and wires under the influence of a transverse magnetic field.